Ameliorative effect of Etlingera calophrys (K.Schum.) rhizome ethanolic extract on high fat diet-induced obese zebrafish - Idrus, Loly Subhiaty; Fakri, Fajar; Rika Hartati,; Vienna Saraswaty,; I Ketut Adnyana, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Obesity is a major factor associated with inflammatory and various metabolic syndromes. Etlingera caloprhys, an Indonesia plant native from Southeast Sulawesi, is traditionally used years as daily food ingredient by local communities. The present paper presents an in vitro and in vivo study related to the anti-obesity effects of Etlingera caloprhys ethanol extract (ECEE). An experiment was conducted to evaluate in vitro pancreatic lipase enzyme (PLE) inhibition and in vivo anti-obesity activity in high fat diet (HFD) induced obese zebrafish fed with 10% w/w and 20% w/w ECEE-HFD were evaluated. To confirm anti-obesity activity, a set of obesity and biochemistry parameters i.e. body weight, body mass index (BMI), triglyceride and blood glucose levels, were monitored. Additionally, gene expression levels related to obesity i.e. adiponectin and PPARγ in visceral adipose tissue (VAT) were also evaluated. The results showed that ECEE significantly (p <0.05) inhibited PLE activity with an inhibition concentration (IC)50 of below 100 μg/mL. The HFD induced obese zebrafish fed with 10% w/w and 20% w/w ECEE-HFD showed decreasing body weight and BMI. The biochemistry parameters of the HFD-induced obese zebrafish fed with 10% w/w ECEE-HFD obviously displayed optimum reduction of triglycerides and blood glucose levels. More importantly, the gene expression confirmed that ECEE suppressed adipogenesis in VAT. Hence, ECEE is suggested as a potent alternative medicine for prevention of metabolic syndromes related to obesity.